Batch 3 IIUM mkitchen students - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohamad Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; et al. (mKitchen, 2022)
This book narrates the journey of Batch 3 IIUM Mkitchen Students. The students started the journey with in-class training on entrepreneurship, business plan development, digital marketing, and cash management. Then, the students had the cooking demonstration on several food trained by trainers of mkitchen. This batch is fortunate to have a permanent space given by the university. JEL Classification: M13 and M15